Data deficiency, taxonomic bias, and economic interests curtail insect and arachnid conservation in the United States - Wes Walsh; Laura L. Figueroa (Proceedings of the National Academy of Sciences, 2026)
Earth is experiencing a biodiversity crisis. Among the declining taxa are insects and arachnids, which account for most of the world’s animal species, and are ecologically and economically vital. Thus, understanding the factors influencing insect and arachnid conservation policies is urgently needed. Here, we review conservation assessments for 46,257 North American insect and arachnid species and examine the factors that affect state and federal legal protections for species in the United States. We find the conservation status of 88.5% of described insect and arachnid species in North America is unknown, and that unassessed insect and arachnid species are unlikely to receive protection. Of US insects and arachnids known to be at-risk throughout their range, 94.7% are not protected by any state or federal law; only 2.5% are protected nationwide under the federal Endangered Species Act compared to 27.7% of range wide at-risk US bird species. Insect and arachnid protections are taxonomically biased, favoring dragonflies and damselflies (Odonata) and butterflies and moths (Lepidoptera) while overlooking other vulnerable taxa. We find that socioeconomic factors are the strongest predictors of state-level conservation policies: states with economies more reliant on mining, quarrying, and oil and gas extraction are less likely to protect insects and arachnids. In states where protections exist, more insect and arachnid species are protected when more residents hold eco-centric values. This quantitative assessment of US insect and arachnid conservation rectifies a previous dearth of data and highlights specific, addressable issues which have left countless species vulnerable to decline and possible extinction.